Employee satisfaction in Kumari bank limited - Saud, Bhagrathi Kumari (Brixton Scholarly Review, 2025)
This study explores employee satisfaction at Kumari bank limited, focusing on key factors influencing job satisfaction and their impact on overall organization performance. Employee satisfaction is critical to maintaining a productive and motivated workforce, which in turn contributes to the success of any financial institution. This study aimed to identify job satisfaction among the employees of Kumari Bank Limited and analysed the factors responsible for job satisfaction. it also examined the levels of satisfaction have towards their job at Kumari Bank Limited. This research made a significant contribution to addressing the problem of job satisfaction in commercial banks. The research study was conducted and analysed using a mixed method which included the interviews, questionnaires and surveys. Data were collected through interviews and questionnaires with employees from different departments. This research was based on primary data, with a sample of 18 Employees from Kumari Bank Limited. The study found that while some in the banking sector were satisfied with their jobs, others were dissatisfied with their current roles.